The relationship between gabbros and I-type granites in the southeast coast of Fujian, South China: Evidence from in situ zircon U-Pb dating, Hf isotopes and whole-rock geochemistry - Qiu, Jian-Sheng; Li, Zhen (2011)
Two representative gabbro–granite complexes from Quanzhou (QZ) and Huacuo (HC) in the southeast coast of Fujian, South China have been selected for a detailed geochronological and geochemical study, aiming to probe the genetic relations between the acid and basic magmas. These complexes are composed predominantly of I-type granitoids, with lesser amounts of hornblende gabbro (<5% of the total igneous rocks). Zircon U-Pb dating yields consistent crystallisation ages of 109 ± 1 and 108 ± 1 Ma for the QZ gabbros and granites, and an age of 111 ± 1 Ma for the HC gabbros, which is contemporaneous with the spatially coexisted HC granites. Both the gabbros and granitoids are enriched in light rare earth elements and large ion lithophile elements (e.g. Rb, Ba, Th and U), and depleted in high field strength elements (e.g. Nb and Ta). Moreover, they show similarly homogeneous Sr–Nd isotopic compositions. All these factors indicate that they are genetically related. Although the Sr–Nd isotopic signatures of the QZ and HC gabbros seemingly point to an enriched mantle source (EM-1), they have highly variable zircon Hf isotopic compositions, with !Hf (t) values ranging from negative to positive (specifically –4.6 to +6.1 for the QZ gabbros and –4.8 to +11.6 for the HC gabbros). On the other hand, their associated granitoids show relatively high whole-rock !Nd (t) values (–2.5 and –4.1 for the QZ and HC granites, respectively), and homogeneous and neutral zircon !Hf (t) values (–1.9 to +1.8 for the QZ granite). Based on an integration of petrography, geochronology and geochemistry, we interpret the parental basic magmas of these gabbros have originated from a depleted mantle source, but experienced a significant crustal contamination by the felsic melts that gave rise to the associated granitoids. Contributions from such a depleted mantle source resulted in the growth of juvenile basaltic lower crust, the partial melting of which generated the parental felsic magmas of the QZ and HC complexes.